Penerapan Metode Edutainment Guna Meningkatkan Kemampuan Mengenal Warna Pada Anak Usia Dini Di TK Al-Hidayah - piraini piraini; Mutia Mawardah (UIN Sultan Maulana Hasanuddin Banten, 2022)
This article is based on the Community Partnership Program (PKM) which seeks to improve the ability to recognize colors in early childhood. The ability to recognize colors is an aspect of cognitive abilities. Early childhood color recognition can stimulate vision in the brain Color can also induce visual sensitivity. This happens because the color of the object is directly or indirectly exposed to sunlight and visible to the eye. The learning strategy aims to make learning can be achieved well, one of which is the Edutainment strategy that can be used in early childhood learning. The purpose of this study is to improve the ability to recognize colors that will be given to TK-Al Hidayah students and provide an interesting approach method. The method used is observation, interviews and lectures. Based on the results of the application of the edutainment learning method, it can be concluded that the program can provide learning and knowledge to children about basic colors, the edutainment method can make it easier for children to understand the material, the edutainment method can also provide a new learning atmosphere for Al Hidayah Kindergarten children and can be used as recommendations for improving learning methods. It is hoped that this research can provide experience and lessons for the author, especially in education. The author hopes that further practice can develop this research more broadly with different methods. Keywords: edutainment, color recognition, early age ReferencesAksakal, N. (2015). Theoretical view to the approach of the edutainment. Journal Procedia -Social and Behavioral Sciences,186,1232-1239. Assyifa, F. N., Rohita, & Nurfadilah. (2020). Pengaruh Video Pembelajaran Interaktif Mengenal Warna Terhadap Kemampuan Kognitif Anak. JIV-Jurnal Ilmiah Visi, 15(2), 137–146. https://doi.org/10.21009/jiv.1502.5Beaty. (2013). Observasi Perkembangan Anak Usia Dini. PT Fajar InterpraDepartemen Pendidikan Nasional.(2005). Kamus Besar Bahasa Indonesia. Gusmita. (2018). Penggunaan Media Gambar Berwarna Dalam Meningkatkan Kemampuan Mengenal Warna IAIN Bengkulu Tahun 2018 M / 1439 H. Hamid, S. M. (2014). Metode edutainment. Diva Press. Hamruni. (2009). Edutainment dalam Pendidikan Islam. UIN Sunan Kalijaga YogyakartaHarun Rasyid. (2009). Mansyur & Suratno. Asesmen Perkembangan Anak Usia Dini. Multi Pressindo. imroatun, imroatun, Fadilatunnisa, A., Hasanah, N., & Rahayu, S. H. (2021). IMPLEMENTASI BERMAIN LEGO SEBAGAI PEMBELAJARAN HARIAN UNTUK PENGEMBANGAN KREATIFITAS ANAK USIA DINI. Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 3(2), 55–67. https://doi.org/10.35473/IJEC.V3I2.1005Lestari, K.W. (2011). Konsep Mengenal Warna. Kencana. Maryani, I., & Nofitasari, A. D. (2018). Efektifitas Metode Eksperimen Terhadap Kemampuan Mengenal Warna Di Kelas a TK Aba Tobayan Sleman. Early Childhood : Jurnal Pendidikan, 2(1), 7–15. https://doi.org/10.35568/ earlychildhood.v2i1.158. Mastija & Wiwik Widajati. (2013). Peningkatan Kemampuan Mengenal Konsep Warna Melalui Permainan Edukatif dengan Styrofoam pada Anak Usia Dini Kelompok A di TK Islam Al Fajar Surabaya. Mastoah, I., & MS, Z. (2020). Kendala Orang Tua Dalam Mendampingi Anak Belajar Pada Masa Covid 19 Di Kota Serang. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 5(2), 121–128. Menteri Pendidikan Nasional. (2009). Peraturan Menteri Pendidikan Nasional Republik Indonesia Nomor 58 Tahun 2009. KemendiknasNurma, N., & Maemonah, M. (2022). Hakikat Agama Dalam Pembentukan Karakter Anak Usia Dini. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 7(1), 29–40. Nuryati, N., Muthmainnah, M., Lubis, H. Z., Talango, S. R., Ibrohim, B., & Nadjih, D. (2021). Metode Role Playing Dalam Meningkatkan Motivasi Berprestasi Anak Usia Dini Selama Masa Learning From Home. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 6(2), 139–148. https://doi.org/10.32678/AS-SIBYAN.V6I2.4649Permata, R. D. (2020). Meningkatkan Kemampuan Mengenal Warna Melalui Permainan Mengelompokkan Bola Warna Pada Anak Usia 4–5 Tahun. Jurnal Teladan: Jurnal Ilmu Pendidikan Dan https://pmat.unirow.ac.id/ journal/index.php/teladan/article/view/117 Pujianti, R., Sumardi, S., & Mulyadi, S. (2021). Perkembangan Sosial Emosional Anak Usia 5-6 Tahun Selama Pembelajaran Jarak Jauh Di Raudhatul Athfal. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 6(2), 117–126. https://doi.org/10.32678/AS-SIBYAN.V6I2.4919.Purwaningsih, E. (2018). Mengenal Warna, Angka, Huruf Dan Bentuk Pada Anak Usia Dini Melalui Animasi Interaktif. Jurnal Ilmu Pengetahuan Dan Teknologi Komputer, 3(2), 203–210. www.bsi.ac.idSantoso. (2018). Penerapan Konsep Edutainment Dalam Pembelajaran Di Pendidikan Anak Usia Dini (PAUD). INOPENDAS: Jurnal Ilmiah Kependidikan, 1(1), 61–68. http://jurnal.umk.ac.id/index.php/pendas/index tama Mandiri.Widiasmoro, E. (2018). Strategi pembelajaran edutainment berbasis karakter. Ar-ruzz Media.